Composing what happened. Issue 12 (2nd December 2022) - Vriezen, Samuel
ABSTRACT: Time and memory in Gertrude Stein are explored using on the one hand a fragment of her play, What Happened; and on the other hand, the conceptual underpinnings of Fourier transforms as applied in musical composition to relate the 'time domain' to the 'frequency domain' in the description of sonic events. The paper sets these concepts to work in a reconstruction of the operation of memory in interaction with real-time events – both the event being remembered and the act of remembering as an event in time itself, with memory being understood as a harmony-like resonance connecting those moments. The concept of 'harmony' here is given a wider understanding, extending from relations between sounds to relations between people (musicians, collaborators). The paper looks in detail at the collaborative diachronic resonances that lead from Stein's attending a birthday party in 1913, through her writing a play, then a collective reading of the play and the collaborative composition of an opera, to the reconstitution in-time of this act of memory in performance, in collaboration with musicians. Finally, the paper provides an answer to an important question raised by Stein on birthday cakes – is a cut a slice?